Assessment of AISI 304 stainless steel by cyaniding process under dry sliding conditions. (2021) - Rohit Sai Krishna, A.; Prudhvi Sri Kalyan, K.; Chandu Prasad Yadav, M.; Saranya, J.; Nookaraju, B. Ch.; Anitha Lakshmi, A.; Prashanth, S.; Subbiah, Ram
Abstract: AISI 304 stainless steel is a austenitic stainless steel which has good corrosion resistance and resistance to pitting. But this metal lacks hardness and it has very poor wear resistance. To improve the mechanical properties of AISI 430 cyaniding process is chosen, which is a case hardening process which improves hardness as well as wear resistance of the material. Here the specimen is shaped in the form of bullets with diameter 10 mm and length 40 mm. Four sets of specimens are taken and out of which three are subjected to liquid cyaniding and the remaining set is kept untreated for comparing the properties with treated specimen. The specimens were treated to 60 min, 90 min, 120 min respectively. The properties of treated and untreated specimen is compared by doing wear test using pin on disc apparatus and also by comparing the microstructures of treated and untreated specimens, which is obtained by Scanning Electron Microscope (SEM images).